Testing the principle of equivalence by supernova neutrinos - Guzzo, M. M.; Nunokawa, H.; Tomas, R. (Elsevier B.V., 2002)
We study the possible impact of the neutrino oscillation which could be induced by a tiny violation of equivalence principle (VEP) on the observation of neutrinos emitted from supernova driven by gravitational collapse. We show that using supernova neutrinos, one can probe very small values of VEP parameters, delta(tau) less than or similar to O(10(-31)) for massless or degenerated neutrinos and delta(tau) less than or similar to O(10(-16)) x (Deltam(2)/10(-5) eV(2)) for massive neutrinos. (C) 2002 Elsevier B.V. B.V. All rights reserved.